The incidence, prevalence and survival of systemic sclerosis in the UK Clinical Practice Research Datalink - Royle, Jeremy G.; Lanyon, Peter C.; Grainge, Matthew J.; Abhishek, Abhishek; Pearce, Fiona A. (Springer, 2018)
Objective: To estimate the incidence, prevalence and survival of systemic sclerosis in the United Kingdom. Methods: We conducted a historical cohort study using data from the Clinical Practice Research Datalink (CPRD). We calculated the incidence and survival of systemic sclerosis between 1994 and 2013 and examined its association with age, sex, and socio-economic status. We calculated point prevalence on 1 July 2013, and examined its association with the same exposures. Results: We identified 1,327 cases with incident systemic sclerosis. Annual incidence was 19.4 per million person-years between 1994 and 2013. The incidence was 4.7 times higher in women than in men, was not influenced by socioeconomic status, and has remained stable over the 20 year study period. The peak age of onset was 55-69 years. Survival at 1, 5 and 10 years was 94.2%, 80.0% and 65.7% respectively. The prevalence was 307 (290-323) per million with the highest prevalence in the 70-84 years age group. We estimate there are currently 1180 new cases of systemic sclerosis each year in the UK, and 19,390 people living with systemic sclerosis. Due to the predicted growth and aging of the population, we predict a 24% increase in incident cases and 26% increase in prevalent cases in 20 years’ time. Conclusion: Our estimates of incidence and prevalence are higher than previously reported in the UK, but similar to recent USA and Swedish studies, and do not support a north-south gradient of the occurrence of systemic sclerosis in Europe.